Collaborative Governance dalam Pemberdayaan UMKM Melalui Pemanfaatan Potensi Alam Menuju Sustainable Tourism di Desa Wisata Taro Kabupaten Gianyar - Wijaya, Komang Adi Sastra; Yudartha, I Putu Dharmanu; Prabawati, Ni Putu Anik; Lukman, Juwita Pratiwi; Dewi, Sang Ayu Nyoman Sinta; Riani, Ni Wayan (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2024)
Taro Village is located in Tegallalang District, Gianyar Regency, which has quite a lot of natural potential that is in demand by tourists and has developed rapidly since it was designated as a Tourism Village in 2017. Taro Tourism Village can be said to be a tourism village that has implemented sustainable tourism. This can be seen from its implementation which tends to emphasize the sustainability aspect. However, the management of the natural potential of Taro Village leaves various gaps of opportunity that have not been utilized by the community, reflected in the absence of typical products of Taro Tourism Village. In carrying out community service activities, namely empowerment targeting the Taro Village Women Farmers Group and MSMEs through the utilization of the natural potential of Taro Village. Collaborative governance practices are carried out by involving three actors, namely the government, the community and the private sector. First, collaboration involving the government through the Village-Owned Enterprise (BUMDes) Sarwada Amertha. Second, the role of the community as a group that is empowered so that they can produce a valuable product and can support sustainable tourism in Taro Tourism Village. We involve the private sector by visiting industries engaged in tourism, such as lodging and resorts that have the potential for us to collaborate with.